Analisis Kebutuhan Belajar Masyarakat Nelayan dalam Penguatan Kapasitas Ekonomi di Wilayah Pesisir Desa Oki Lama Kabupaten Buru Selatan - Arjun Latbual; R Tutupary; Junita L Kundre (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the learning needs of fishing communities in Oki Lama coastal area, Namrole District, South Buru Regency. The study employed a descriptive qualitative approach involving fishermen groups, village officials, and coastal community members as research informants. Data were collected through in-depth interviews, observations, and questionnaires, and analyzed using descriptive qualitative techniques. The findings reveal that fishing activities in Oki Lama are still dominated by traditional practices and are highly dependent on seasonal and weather conditions, resulting in unstable household incomes. The study identified several priority learning needs among fishing communities, including fish processing skills, marketing strategies, household financial management, and the utilization of appropriate fisheries technology. In addition, limited access to government empowerment programs and inadequate institutional support remain major challenges for coastal communities. The study emphasizes that community learning programs should be implemented through participatory and practice-based nonformal education approaches that are relevant to local socio-economic conditions. These findings contribute to the development of community empowerment strategies for improving the economic resilience of coastal fishing communities.